Emergency General Surgery: Predicting Morbidity and Mortality in the Geriatric Population - Elamin, Abubaker; Tsoutsanis, Panagiotis; Sinan, Laith; Tari, Seyedh Paniz Hashemi; Elamin, Wafa; Kurihara, Hayato (The Surgery Journal, 2022)
Introduction Numerous scoring systems have been created to predict the risk of morbidity and mortality in patients undergoing emergency general surgery (EGS).In this article, we compared the different scoring systems utilized at Humanitas Research Hospital and analyzed which one performed the best when assessing geriatric patients (>65 years of age). The scoring systems that were utilized were the APACHE II (Acute Physiology and Chronic Health Evaluation II), ASA (American Society of Anesthesiologists), ACS-NSQIP (American College of Surgeons-National Surgical Quality Improvement Program), Clinical Frailty Score, and the Clavien–Dindo classification as control.Materials and Methods We compiled a database consisting of all patients over the age of 65 who underwent EGS in a consecutive 24-month period between January 1, 2017 and December 31, 2018. We used the biostatistical program “Stata Version 15” to analyze our results.Results We found 213 patients who matched our inclusion criteria. Regarding death, we found that the ACS-NSQIP death calculator performed the best with an area under the curve of 0.9017 (odds ratio: 1.09; 95% confidence interval: 1.06–1.12). The APACHE II score had the lowest discriminator when predicting death. Considering short-term complications, the Clavien–Dindo classification scored highly, while both the APACHE II score and Clinical Frailty Score produced the lowest results.Conclusion The results obtained from our research showed that scoring systems and classifications produced different results depending on whether they were used to predict deaths or short-term complications among geriatric patients undergoing EGS.
Keywords: emergency general surgery; surgery; elderly; scoring systems; APACHE II; ASA; ACS-NSQIP; clinical frailty score; Clavien–Dindo